ANALISIS PENGARUH VARIABEL FUNDAMENTAL DAN MAKROEKONOMI TERHADAP EKSPOSUR EKONOMI (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2015-2017 ) - Yoseva Maria Pujirahayu Sumaji (Politeknik Ubaya, 2019)
Globalization is growing rapidly, inter-state economic relations will become intertwined and increase flow of trade of goods and money as well as capital between countries. Changes in macroeconomic indicators occurring in other countries will indirectly impact the country’s economic indicators. Indonesia is one of the countries with the largest potential land for the development of industrial sectors. This is related to the many resources in Indonesia for both raw materials and labour. The results of Indonesia’s manufacturing industry increasingly propagate into world markets. The Central Statistic Agency (BPS) records the Indonesian economy in cumulative growth of 5.78 percent in 2013. The achievement of Indonesia’s economic growth is still far below China and India, however, in terms of economic growth, Indonesia is among the three major. The number of middle class citizens reached 36 million people and was relatively productive. While the manufacturing industry becomes an important component to economic exposure (study on the IDX-listed manufacturing company 2015-2017). There are 120 non-financial companies in Indonesia. The sampling technique in this study is nonprobability sampling (unrandomized withdrawal of samples). The data collection technique in this study is to use the documentation method published by the Indonesian Stock Exchange (IDX). The analysis of the research data includes descriptive statistical analysis, inferential statistical analysis and hypothesis testing.